Transformer oil diagnostic by using an optical fibre system: a review - Khallawi, Alaa Razzaq; Zainuddin, Hidayat; Hanaffi, Farhan; Chyad, Radhi Muhssin (The Institution of Engineering and Technology, 2019)
High-voltage transformers are essential for power systems, particularly in the transmission and distribution sectors. The reliability of this equipment typically depends on their insulation condition. Thus, considerable attention must be accorded to the development of diagnostic and monitoring systems for predicting the condition of transformer oil. At present, several electrical, physical and chemical diagnostic techniques have been applied to transformer condition monitoring. This study presents a review of the application of optical sensors to transformer condition monitoring. Optical-sensor-based monitoring of various parameters of transformer oil as part of transformer condition monitoring is discussed. The classification and sensing principles of optical sensors are also reviewed.